1998
DOI: 10.1159/000007514
|View full text |Cite
|
Sign up to set email alerts
|

Diet Supplemented with Yoghurt or Milk Fermented by <i>Lactobacillus casei</i> DN-114 001 Stimulates Growth and Brush-Border Enzyme Activities in Mouse Small Intestine

Abstract: The nutritional benefits of lactic acid bacteria in fermented dairy products have been well documented, especially in terms of weight gain and feed efficiency, but not in terms of small intestine adaptation. The effects of a diet supplemented (30% wt/wt) with milk fermented either by Lactobacillus casei DN-114 001 or yoghurt for 3 or 15 days were investigated in the small intestine of mice by morphometry, kinetic analysis and determination of brush-border enzyme activities. Results were compared with those obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…This increase in PCs was associated with a rise of lysozyme and rdefa5 expression. In agreement with our results, Thoreux et al demonstrated that the number of PCs significantly rose in the three portions of the small intestine of mice receiving a diet supplemented with yoghurt [32]. The mechanism responsible for this effect was not further investigated however.…”
Section: Discussionsupporting
confidence: 90%
“…This increase in PCs was associated with a rise of lysozyme and rdefa5 expression. In agreement with our results, Thoreux et al demonstrated that the number of PCs significantly rose in the three portions of the small intestine of mice receiving a diet supplemented with yoghurt [32]. The mechanism responsible for this effect was not further investigated however.…”
Section: Discussionsupporting
confidence: 90%
“…This interaction likely leads to improved intestinal protection and may have implications for improved intestinal health. Similar observations have been made in vivo, with goblet cell hypertrophy and hyperplasia of paneth and goblet cells being induced with the administration of yoghurt fermented with L. casei (Thoreux et al, 1998). Fermentation products of L. rhamnosus also suppress the release of prostaglandins (mediators of acute and chronic inflammation in response to IL-1β) through an opioid receptor mediated response in intestinal epithelial cells (Fiander et al, 2005).…”
Section: Bioactive Peptidessupporting
confidence: 66%
“…As noted, these changes in microbiota would be independent of the fiber effects and would affect mainly the upper part of the intestinal tract. Direct stimulation of intestinal microbial populations with fermented foodstuffs increases the number of PCs in the upper intestine of mice (Thoreux et al 1998), but the general configuration and secretory properties of the PCs along the intestine match the increasing density of bacteria towards the ileum (Darmoul & Ouellette 1996). The composition of the whole diet has shown to exert an effect on the jejunal enteroendocrine-cell population that can be distiguished from the effects of the associated microbiota (Sharma & Schumacher 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The role of PCs in the intestine cell concert is not clearly understood because experiments on cell ablation in mice revealed no alteration in the main variables the PCs are supposed to regulate (Garabedian et al 1997). Moreover, PC activity has been shown to vary in accordance with some specific components of the diet (Masty & Stradley 1991;Thoreux et al 1998) and as a function of the alimentary condition of the subjects (Ahonen & Penttila 1975). Paneth cells also contain the enzyme deoxyribonuclease (Shimada et al 1998), which may be related to their microbicidal role and to the digestion of foodstuffs.…”
Section: Introductionmentioning
confidence: 99%